Antimicrobial Activity of Punica granatum, Citrus sinensis, Musa acuminata Fruit Peel and Applications in Food Preservation - Poojara, Rashmi H; N R, Gopika; Ashok, Unnimaya (Asian Journal of Biological and Life Sciences)
This study evaluated the antimicrobial, antifungal, antioxidant, and phytochemical properties of ethanolic extracts derived from the peels of Punica granatum (pomegranate), Citrus sinensis (orange), and Musa acuminata (banana). The antimicrobial and antifungal activity against E. coli and Aspergillus niger was assayed using the agar well diffusion method. Antioxidant activity of the fruit peel extract was assessed using DPPH radical scavenging activity. The assay for total antioxidant capacity was utilized to verify the antioxidant potential and the phytochemical content, including total phenols and flavonoids. The study findings indicate that Citrus sinensis peel exhibited strong antibacterial and antifungal activity against E. coli and Aspergillus niger and facilitated shelf-life extension of tomato paste. The phytochemical analysis revealed that Punica granatum peels comprised bioactive compounds, thus supporting that fruit peels, often discarded as waste, can be effectively repurposed as natural preservatives in food systems as a sustainable alternative to chemical preservatives.
Keywords: Antimicrobial activity; Antioxidants; Fruit peels; Food preservation.